Analisis Yuridis Normatif Terhadap Putusan Nomor 9/Pid.b/2024/PN Pemalang: Studi Kasus Pembunuhan Berencana di Kabupaten Pemalang - Pambudi, Phokus Rilo; Yusuf, Hudi (Media Hukum Indonesia (MHI), 2025)
This study analyzes the decision of the Pemalang District Court Number 9/Pid.B/2024/PN Pml in a premeditated murder case. This study aims to assess the suitability of the decision with the elements of Article 340 of the Criminal Code and Article 181 of the Criminal Code which are the basis for the judge's considerations. The method used is a normative legal analysis of the trial facts, evidence, and legal considerations taken by the panel of judges. The results of the study indicate that this decision has fulfilled the elements in Article 340 of the Criminal Code and Article 181 of the Criminal Code, including the existence of planning before carrying out the crime. However, there are several aspects that can be used as evaluation material in enforcing similar cases in the future. This case not only shows how the legal system works in dealing with serious crimes, but also reveals new social dynamics due to the development of information technology, especially social media. Online acquaintances through platforms such as Facebook and Instagram have become the starting point for criminal acts, including murder. This phenomenon poses new challenges in the legal evidence process, especially regarding the perpetrator's intentions, motives, and planning. The low Human Development Index (HDI) in Pemalang Regency, especially in the aspects of education and health, also exacerbates the vulnerability of society to crimes that originate from online interactions. Low digital literacy and legal understanding are the main contributing factors. The results of this study are expected to contribute to the development of criminal law and better legal protection efforts for victims of crime, both in domestic and digital context